Influence of Knowledge and Attitude on Lifestyle Practices Among Seventh-Day Adventists in Metro Manila, Philippines - Galvez, Cesar Augusto (Journal of religion and health, 2021)
This cross-sectional study examined the influence of knowledge and attitude on lifestyle practices (KAP) of the five dimensions of the Adventist Health Message (AHM5D). A sample of 1442 respondents was drawn from seven Seventh-day Adventist Churches in Metro Manila, Philippines. Hierarchical multiple regression showed that the social dimension of knowledge and the physical, spiritual, and social dimensions of attitude, significantly influenced the practices of AHM5D (β = − .056, p = .037; β = .236, p < .001; β = .211, p < .001; β = .145, p < .001, respectively), with r2 = .334. These findings suggest more effective interventions in the AHM5D promotion.